Representasi politik Dayak: Kajian ideologi dan kekuasaan dalam cerita rakyat Kalimantan Timur - Nugroho, Bayu Aji; Yusriansyah, Eka (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This research examines the representation of power and ideology in Dayak folklore from East Kalimantan using the theoretical frameworks of Michel Foucault and Antonio Gramsci. Folklore is understood as a symbolic arena that records power relations in spiritual, customary, moral-ecological, and political forms. Data were collected from Dayak folktales circulating in East Kalimantan and analyzed qualitatively through a descriptive thematic approach. The findings reveal that spiritual power (as in the tale of Danau Aco), customary authority (Temputn Tolakng), and moral-ecological power (Anak Buaya) function to establish social rules and cultural legitimacy. Meanwhile, the tale of Sumbang Lawing emphasizes the importance of political legitimacy through counter-hegemony against tyrannical figures, Ikan Baung Putih generates moral-ecological regulations in the form of river taboos, and Sri Bangun illustrates colonial trauma shaping a defensive communal identity. This study concludes that Dayak folklore is not merely a moral narrative but also a political-cultural text that represents hegemony, resistance, and collective identity. It highlights folklore as both a medium of negotiating power and a cultural archive in the context of social change in East Kalimantan.